A convenção de condomínio e as restrições aos direitos dos condôminos dela decorrentes - Elias Filho, Rubens Carmo (2012)
The study of condominium bylaws and its ensuing restraints to building occupants rights aims to assess the legal grounds for such restrictions, which impose affirmative and negative covenants capable of significantly altering the traditional exercise of ownership rights, particularly the voluntary co-ownership and multi-ownership condominium systems. The validity of such restraints on condominium, brought about by different enjoyment and fruition parameters and limitations on ownership rights, is often disputed in light of the Federal Constitution, on the grounds that ownership constitutes fundamental civil rights. Many quite polemical, however commonplace, restraints addressed in this paper arise from either daily issues in multi-ownership condominia or the different uses of the new shared building facilities. We deem it timely to consider if such restraints indeed impose limitations on ownership rights or rather reveal an incipient understanding on the theme, justifying the research on legal writings and case law intended herein. This paper attempts to present the limitations to the exercise of ownership rights in property held pro indiviso, such as restraints imposed on the owner in either voluntary co-ownership or multi-ownership condominium, two of the most recurring expressions in modern ownership laws. It also assesses what such limitations are, how they are imposed, and what their effectiveness before occupants, third parties and prospective owners can be. To achieve this, we assess the restraints in light of propter rem covenants and speculate whether such type should require the restraints and how they could be routinely imposed both on occupants of multi-ownership condominium, by means of its due inclusion on condominium bylaws, and on holders of voluntary jointly-owned property, about which the law states no registration procedures for condominium bylaws. The study is presented in three modules. The first concerns structural questions on ownership rights, its restrictions and social purpose; the second, the definitions and effects of voluntary co-ownership and multi-ownership condominia; the third, an in-depth look at the restraints imposed on occupants and owners, in a range of daily situations of sheer indignation despite its compliance with applicable laws and resonance with the social and economic context in condominia, grounded in social purpose, ethics, and good faith